From Hotelling to Load Balancing: Approximation and the Principle of Minimum Differentiation - Feldotto, Matthias; Lenzner, Pascal; Molitor, Louise; Skopalik, Alexander (Proceedings of the 18th International Conference on Autonomous Agents and MultiAgent Systems)
Competing firms tend to select similar locations for their stores. This phenomenon, called the principle of minimum differentiation, was captured by Hotelling with a landmark model of spatial competition but is still the object of an ongoing scientific debate. Although consistently observed in practice, many more realistic variants of Hotelling's model fail to support minimum differentiation or do not have pure equilibria at all. In particular, it was recently proven for a generalized model which incorporates negative network externalities and which contains Hotelling's model and classical selfish load balancing as special cases, that the unique equilibria do not adhere to minimum differentiation. Furthermore, it was shown that for a significant parameter range pure equilibria do not exist. We derive a sharp contrast to these previous results by investigating Hotelling's model with negative network externalities from an entirely new angle: approximate pure subgame perfect equilibria. This approach allows us to prove analytically and via agent-based simulations that approximate equilibria having good approximation guarantees and that adhere to minimum differentiation exist for the full parameter range of the model. Moreover, we show that the obtained approximate equilibria have high social welfare.

Dynamic control of mode modulation and spatial multiplexing using hybrid metasurfaces - Lin, Zemeng; Huang, Lingling; Zhao, Ruizhe; Wei, Qunshuo; Zentgraf, Thomas; Wang, Yongtian; Li, Xiaowei (Optics Express)

Wikipedia Text Reuse: Within and Without - Alshomary, Milad; Völske, Michael; Licht, Tristan; Wachsmuth, Henning; Stein, Benno; Hagen, Matthias; Potthast, Martin (Advances in Information Retrieval)
We study text reuse related to Wikipedia at scale by compiling the first corpus of text reuse cases within Wikipedia as well as without (i.e., reuse of Wikipedia text in a sample of the Common Crawl). To discover reuse beyond verbatim copy and paste, we employ state-of-the-art text reuse detection technology, scaling it for the first time to process the entire Wikipedia as part of a distributed retrieval pipeline. We further report on a pilot analysis of the 100 million reuse cases inside, and the 1.6 million reuse cases outside Wikipedia that we discovered. Text reuse inside Wikipedia gives rise to new tasks such as article template induction, fixing quality flaws, or complementing Wikipedia's ontology. Text reuse outside Wikipedia yields a tangible metric for the emerging field of quantifying Wikipedia's influence on the web. To foster future research into these tasks, and for reproducibility's sake, the Wikipedia text reuse corpus and the retrieval pipeline are made freely available.

Essays on Drivers and Economic Outcomes of Online-Reviews - Gutt, Dominik

Post-Quantum Secure Group Signatures - Porzenheim, Laurens Alexander

Automated testing of NFV orchestrators against carrier-grade multi-PoP scenarios using emulation-based smoke testing - Peuster, Manuel; Marchetti, Michael; García de Blas, Gerardo; Karl, Holger (EURASIP Journal on Wireless Communications and Networking)

Bundling in a Distribution Channel with Retail Competition - Heinzel, Joachim Maria Josef
We analyze the incentives for retail bundling and the welfare effects of retail bundling in a decentralized distribution channel with two retailers and two monopolistic manufacturers. One manufacturer exclusively sells his good to one retailer, whereas the other manufacturer sells his good to both retailers. Thus, one retailer is a monopolist for one product but competes with the other retailer in the second product market. The two-product retailer has the option to bundle his goods or to sell them separately. We find that bundling aggravates the double marginalization problem for the bundling retailer. Nevertheless, when the retailers compete in prices, bundling can be more profitable than separate selling for the retailer as bundling softens the retail competition. The ultimate outcome depends on the manufacturers’ marginal costs. Given retail quantity competition, however, bundling is in no case the retailer’s best strategy. Furthermore, we show that profitable bundling reduces consumer and producer surplus in the equilibrium.
Keywords: retail bundling; leverage theory; double marginalization

Scheduling Algorithms for Multi-Operation Jobs with Setups on a Single Machine - Pukrop, Simon

Personal Cross-Platform Reputation - Blömer, Johannes; Löken, Nils (Security and Trust Management, STM 2019)
We propose a novel personal reputation system for cross-platform reputation. We observe that, in certain usage scenarios, e.g. crowd work, the rater anonymity property typically imposed on reputation systems is not necessary. Instead, we propose a relaxed notion of rater anonymity that is more applicable in the crowd work scenario. This allows us to construct a secure personal reputation system from simple cryptographic primitives.

Dynamic Searchable Encryption with Access Control - Blömer, Johannes; Löken, Nils (12th International Symposium on Foundations and Practice of Security, FPS 2019)
We present a searchable encryption scheme for dynamic document collections in a multi-user scenario. Our scheme features fine-grained access control to search results, as well as access control to operations such as adding documents to the document collection, or changing individual documents. The scheme features verifiability of search results. Our scheme also satisfies the forward privacy notion crucial for the security of dynamic searchable encryption schemes.